The Effect of Human Resource Quality, Motivation, Discipline and Career Development on Job Satisfaction and Their Impact on the Performance of Transjakarta Employee - Efendi, Sugito; Firmansyah, Deni (PINISI Discretion Review, 2021)
This study aims to analyze the effect of HR Quality, Motivation, Discipline and Career Development on job satisfaction and its impact on the performance of Transjakarta employees. This study uses a survey method by distributing questionnaires to Transjakarta employees as respondents. Quantitative research method with Structural Equation Modeling (SEM) analysis technique with Amos application. The sample in this study were 183 respondents. The results showed that the quality of human resources, motivation and career development directly have a positive and significant effect on job satisfaction, while career development directly have a positive and significant effect on performance of transjakarta employee.Â